'We're equal to the Jews who were destroyed. [. . .] Compensate us, too'. An affective (un)remembering of Germany's colonial past?. (April 2022) - Rausch, Sahra
Following the globalisation of Holocaust memory in the 1990s, references to National Socialist crimes turned into a practise initiated by postcolonial memory carriers to claim recognition and reparation for colonial crimes – often by taking legal steps to qualify colonial crime a crime against humanity. This article argues that the globalised Holocaust memory established a distinctive emotional order. Consequently, marginalised memory groups align with this order to find a voice in official memory politics. The article examines emotional discourses in the OvaHerero class actions against Germany filed in 2001. It shows how media coverage hindered the recognition of colonial crimes when compared with the Holocaust. However, a diachronic contrast with the analysis of the renewed lawsuit filed this time by representatives of the OvaHerero and the Nama in 2017 shows how emotional discourses changed over time and transformed both colonial and Holocaust memory.